House full: Silent film genre, exhibition and audiences in south India - Stephen Hughes (Indian Economic Social History Review 2006; 43; 31, 2006)
This article explores how genre matters for the history of cinema audiences in south India. I focus on the development of silent film genre categories in south India during the 1920s as they were used according to the local conditions to help imagine, define and cultivate cinema audiences. I argue that from the late- 1910s, film genre classifications helped exhibitors and film critics to conceive of, calculate and socially differentiate the steadily growing audiences for cinema. Using material from archival sources and newspapers.advertisements, reviews and film criticism.this article documents how the emergence of film genre categories and their subsequent refinement through the 1920s addressed and articulated a stereotyped sociology of local film audiences in Madras. At the beginning of the 1920s there were three main classifications of films recognised in the local cinema market of Madras.serials, short dramas and Indian films. For almost a decade these three categories broadly covered the range of films available in Madras. Local exhibitors and film critics saw each type of film as part of a changing system of complementary and contrasting entertainment alternatives corresponding to definitive kinds of local audiences. As there are few sources and little scholarship which can help deal with early film audiences, the history of film genres offers unique insight into how those in Madras imagined the always indeterminant social reality of film audiences.